“We want to kill caribou, not to live with them”: Inuit Cosmology and Resistance to Herding - Laugrand, Frédéric (Brill, 2023)
This paper explores the cosmological foundation of Inuit rejection of herding and the primal relationships of migratory caribou and local spirits called ijirait. The study is drawing on classical ethnographical materials and oral sources collected in the Canadian eastern Arctic. Information was recorded from Inuit Elders between 1997 and 2011. The question of herding animals, specifically caribou and reindeer, emerged in the early 1920s when Saami herders were brought to Baffin Island. For various reasons, this adventure turned into a major failure. A closer look at Inuit perception of caribou illuminates the ontological foundations of Inuit’s historical and continued resistance to and resentment of herding. In the Canadian Arctic, now Nunavut, Inuit remain attached to hunting the caribou, which they refer to as ‘the lice of the earth’. They connect the caribou to a master spirit (inua) or God, and often associate caribou with the deceased and mountain spirits (ijirait). With this cosmology, and given that hunting and herding involve divergent ideas about animals’ agency and human–animal relationships, transforming Inuit hunters of caribou into herders seems a very difficult task. For Inuit, caribou cannot be mastered or domesticated, and they cannot be ‘products’. They are ‘subjects’ to be eaten and respected. Their paths were object of many rules in order to let the caribou go their proper way. Disrespect would trigger starvation. Hunting caribou was – and to a large extent still is – considered the only way to preserve them.